PENGEMBANGAN MEDIA LOOSE PARTS “AQUARIUM AJAIB” UNTUK MENGEMBANGKAN KREATIVITAS ANAK USIA DINI - Karomah, Rosi (EDUCHILD (Journal of Early Childhood Education), 2025)
Fun learning activities will increase children's willingness to express themselves in the form of works. Loose part media "Magic Aquarium" is one of the media that can be used to develop creativity in early childhood. The research method uses R&D (Research and Development) using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). The development carried out is based on an understanding of the concepts contained in the form of works. Media "Magic Aquarium" can be used in a variety of themes, all things can be made in this media. Children's creativity will develop and will affect their quality of life in making decisions to solve problems.